2020
DOI: 10.3390/biology9030052
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated Wnt-11 and miR-21 Expression Trigger Epithelial Mesenchymal Transition in Aggressive Prostate Cancer Cells

Abstract: Prostate cancer (PCa) is the second-leading cause of cancer-related death among men. microRNAs have been identified as having potential roles in tumorigenesis. An oncomir, miR-21, is commonly highly upregulated in many cancers, including PCa, and showed correlation with the Wnt-signaling axis to increase invasion. Wnt-11 is a developmentally regulated gene and has been found to be upregulated in PCa, but its mechanism is unknown. The present study aimed to investigate the roles of miR-21 and Wnt-11 in PCa in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…miR-21 has been reported to be upregulated and to promote metastasis in several tumor types [17][18][19][20]. Our previous studies showed that miR-21 is involved in cancer cell invasion and differentiation [21][22][23][24].…”
Section: Introductionmentioning
confidence: 97%
“…miR-21 has been reported to be upregulated and to promote metastasis in several tumor types [17][18][19][20]. Our previous studies showed that miR-21 is involved in cancer cell invasion and differentiation [21][22][23][24].…”
Section: Introductionmentioning
confidence: 97%
“…A number of studies have provided evidence for the therapeutic potential of miRNAs in a wide variety of human cancers, including PCa (30,31). The proposed functional miRNAs exert therapeutic potential by regulating tumor cell biological processes, such as cell proliferation, migration and invasion (32).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we had reported that the downregulation of Wnt-11 reduced cell migration and invasion in PCa [36]. We wanted to clarify whether this effect of Wnt-11 was JNK pathway-dependent.…”
Section: Effect Of Silencing Wnt-11 On Cellular Migrationmentioning
confidence: 99%
“…Since we established a link between cell death and JNK signalling, we then wanted to check whether the effect was regulated by Wnt-11. We have previously reported that Wnt-11 is involved in both NED and EMT differentiation in PCa [20,36]; however, how the signals are carried to the downstream target genes are unknown. To test whether the JNK pathway is responsible for Wnt-11 regulated cellular differentiation in PCa, we adopted PC-3 cells as a model, as they express the highest level of Wnt-11 mRNA.…”
Section: Wnt-11 Promotes Emt In Pca Cells Via Jnk Signallingmentioning
confidence: 99%